Update on Novel Non-Operative Treatment for Osteoarthritis: Current Status and Future Trends - Chen, Tao; Weng, Weidong; Liu, Yang; Aspera-Werz, Romina H.; Nüssler, Andreas K; Xu, Jianzhong (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a leading cause of pain and disability which results in a reduced quality of life. Due to the avascular nature of cartilage, damaged cartilage has a finite capacity for healing or regeneration. To date, conservative management, including physical measures and pharmacological therapy are still the principal choices offered for OA patients. Joint arthroplasties or total replacement surgeries are served as the ultimate therapeutic option to rehabilitate the joint function of patients who withstand severe OA. However, these approaches are mainly to relieve the symptoms of OA, instead of decelerating or reversing the progress of cartilage damage. Disease-modifying osteoarthritis drugs (DMOADs) aiming to modify key structures within the OA joints are in development. Tissue engineering is a promising strategy for repairing cartilage, in which cells, genes, and biomaterials are encompassed. Here, we review the current status of preclinical investigations and clinical translations of tissue engineering in the non-operative treatment of OA. Furthermore, this review provides our perspective on the challenges and future directions of tissue engineering in cartilage regeneration.